Field Verification of Bridge Natural Frequency Identification from Acceleration Response of Passenger Car - อาสนจินดา พัทรพงษ์ (Srinakharinwirot University Engineering Journal, 2018)
This research studied bridge natural frequency identification form a passenger car’s acceleration response by field testing. The research aimed to propose the analytical process and the appropriate testing scenario. In addition, effect of relevant parameters was studied. The field test was carried out with short span reinforce concrete bridges and passenger car as the test vehicles. The bridge natural frequency can be identified by using indirect method from the proposed process of signal analysis of the measured acceleration response. Regarding to the result of experimental study, it was revealed that the proposed process was able to identify the bridge fundamental frequency in every experimental case. Moreover, it was observed that the analyzed frequencies were exactly the same to those obtained from the direct measurement to the bridge.